Biodiesel Feedstocks, Production and Applications - Fang, Zhen (IntechOpen, 2012)
This book focuses on the development of biodiesel systems from the production of feedstocks and their processing technologies to the comprehensive applications of both by-products and biodiesel. It should be of interest for students, researchers, scientists and technologists.